PELATIHAN STUDY SKILLS UNTUK PRESTASI AKADEMIK MAHASISWA - Laili, Latifatul; Andrianto, Sonny (JIP (Jurnal Intervensi Psikologi), 2023)
The educational system, teaching methods, types of assignments, and the learning environment pose distinct challenges, requiring students to possess study skills appropriate to the learning context. There is a growing body of literature that recognizes the positive influence of study skills on students' academic performance. However, research focusing on the effectiveness of study skills programs is still limited. This study analyzes the effects of study skills training on increasing student academic performance. A quasi-experiment was employed using a one-group pretest and posttest design with 59 psychology students. Data for this study were collected using student GPAs before and after the intervention. The study shows that study skills training is effective in increasing student academic performance. Higher education institutions can apply study skills training for students to optimize their academic performances. Further research is needed.